New Paradigm for Determining Necrosis, Stage and Prognosis of Severe Acute Necrotizing Pancreatitis - Dashbazar, Erdenebold; Nachin, Baasanjav; Baasanjav, Batbold; Chimedtseye, Puntsag; Mashbaljir, Ganbaatar; Seseer, Altankhuyag (Central Asian Journal of Medical Sciences, 2021)
Objective: To determine the clinical features and diagnostic parameters of acute alcohol-induced pancreatic necrosis to develop a new system to assess the severity of acute pancreatitis, diagnose necrotic inflammation, and understand prognosis. Methods: We performed a retrospective chart review of patients admitted to the General Surgery Department and Gastroenterology Department of The Third Central Hospital, and The First Central Hospital in Ulaanbaatar from November 1, 2008, to January 1, 2020, admitted with acute pancreatitis, gathering clinical data using a structured form. From these data, we developed a new scoring system. Results: The median age of patients with acute necrotic pancreatitis was 43 (range 25-71) years, with the majority (87.4%) ages 26 to 60. Of the 31 deaths reported in the study, 24 (77.4%) were hospitalized more than 72 hours after the onset of the disease. Using the new evaluation system, 12 out of 122 patients were classified as class A (score 0-3), 69 (56.5%) were class B (score 4-6), and 41 (33.6%) of the patients were class C (score ≥7) points. Conclusion: The evaluation system we developed aids with early diagnosis, progression and prognosis of severe forms of acute pancreatitis. It is easy to score, and it is possible to score using information available in Mongolia’s secondary and tertiary hospitals.